KEBIJAKAN HUKUM PIDANA DALAM MENANGGULANGI TINDAK PIDANA PENISTAAN AGAMA DI INDONESIA ( Studi Pada Kelompok Gafatar) - OLOAN SIAHAAN, S.I.K. NPM.A2021131074, JURNAL MAHASISWA S2 HUKUM UNTAN (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACTThis thesis discusses the Criminal Law Policy in Tackling the Crime of Defamation in Indonesia (Study on Gafatar Group). The approach method used in this research is sociological normatife approach. From the results of this thesis research, it can be concluded that the form of religious blasphemy done by Gafatar group at this time, Gafatar group is not obligated to pray five times, fasting Ramadan and pilgrimage and having different syahadat. The Gafatar group also disbelieves others who are not their group. Pillars of Islam for example there are five, they Gafatar Group claim Islam, but not praying, fasting, and not pilgrimage, Gafatar does not recognize the Prophet Muhammad as Prophet and Rasul and Sentences Syahadatain are taught are: Asyahadu An Laa Ilaaha illaallahu, Wa Asyhadu Annal Massih Al-Mau'uud Rasulullah (I testify that There is no right in worship except Allah, and I testify that Al-Masiih is promised is the Messenger of Allah). As for Al-Masiih which is promised here means Ahmad Musadeq. Should the legal arrangement of the Crime of Penidaan Religion in Indonesian legislation Arrangement in the Criminal Code (KUHP) in Article 156a of the Indonesian Penal Code reads entirely: